Scenedesmus dimorphus تأثير بعض العناصر الثقيلة في قيم الامتصاصية لمزارع الطحلب الأخضر - باهل جدعان, دنيا; منحر علكم, فؤاد (University of Thi-Qar Journal of Science, 2010)
The present study was concerned with the effect of some heavy metals (Lead, Cadmium, Copper, and Zinc) and their toxicity individually on the growth of green alga Scenedesmus dimorphus which belongs to the phylum of Chlorophyta .This was achieved depending on the absorption values to measure the living biomass of the alga,and then computing the growth average and doubling time when exposing the alga to these metals.The effective median concentration EC50 of each of these four metals were also computed.The concentrations (15, 20, 25, 30)mg/l of lead were used. Results showed that exposing the alga to the concentration (30) mg/l caused an acute decrease in growth. The other concentration (15, 20, 25)mg/l also led to a gradual decrease in growth. Treating the alga with(0.05, 0.1, 0.5, 1)mg/lconcentration of Cadmium the number of cells decreased in case of three concentration (0.05, 0.1, 0.5) mg/l. The decrease in growth was greater and clearer in case of the concentration (1)mg/l concentration Cadmium.As for Copper the concentrations (0.5, 1, 1.5, 2)mg/l and the concentration (2)mg/l had the greatest effect in deceasing growth. Results also showed that theconcentration (3)mg/l of zinc had the greatest effect in decreasing the growth on compared with the other concentration (0.7, 1, 2, 3)mg/l.